Edukasi Etika Batuk Efektif di Era New Normal Pandemi Covid-19 Di Desa Solonsa Kecamatan Wita Ponda Kabupaten Morowali: Edukasi Etika Batuk Efektif di Era New Normal Pandemi Covid-19 Di Desa Solonsa Kecamatan Wita Ponda Kabupaten Morowali - Nour Sriyanah; Andi Riska (LPPM STIK Makassar, 2021)
Background: Low knowledge of effective cough ethics can lead to uncontrolled transmission of the corona virus. Knowledge of effective cough ethics can be improved by conducting health education. Media is needed when conducting health education to facilitate the delivery of information. This means that people who serve their activities return in the Covid-19 situation, but still pay attention to health protocols. Coughing is a reaction that occurs in the cells in the airways behind the esophagus being irritated. This research is also given in a pre-test and post-test design. Aims: To provide respondents with an understanding of the ethics of effective coughing. Methods: In this outreach using descriptive methods using pre-test and post-test questionnaires. Results: From the counseling that has been done to respondents in Solonsa Village, there were 8 respondents who had low knowledge (66.66%) and 4 respondents with sufficient knowledge (33.33%). Conclusion: After counseling was carried out, there was an increase in the knowledge of respondents who had attended the counseling, which increased to 10 respondents (83.33%) with sufficient knowledge and 2 respondents (16.66%) who had sufficient knowledge.